Educação de mestiços em famílias inter-raciais - Brito, Angela Ernestina Cardoso de (2003)
This study aims at aprehending how and in what circumstances families formed by couples of different ethnic-racial origins, being one black and one white, prepare and/or assist their children to face the discrimination the might undergo in consequence of racism againt afro-americans. In oerder to achieve the goal, parents and children of two interracial families were interviewed, in a total of seven interviews. We tried to deepen the knowledge on socilization of mixed offsprings within interracial families, from the statements of the parents and the child. The data obtained and analyzed allow us to conclude that the families use up some strategies to assist hteir children in facing the problem of racism and racial discrimination, even though there are difficulties in elaborating them, and they do not constitute, at least apparently, a priority in children education. However, it was possible to observe that there is a construction of racial belonging, and orientation on possible discriminatory acts kids may undergo. Thus, the orientation is associated to discriminatory experiences lived by the children within the expanded family, at school, on the street, in clubs, being attached to strong affective bonds.